Triple Elimination Screening Examination Results for Pregnant Women of Healthy Reproductive Age in First Trimester at Lebdosari Community Health Center, Semarang City - Nissa Aullya; Fitriani Kahar (International Journal of Educational and Life Sciences, 2024)
Pregnant women are one of the populations at risk of contracting HIV infection, syphilis and Hepatitis B. The prevalence of HIV/AIDS transmission from mother to child is 20-50%, of which 5-10% occurs during pregnancy. Syphilis transmission is 69-80% and Hepatitis B transmission is more than 90% with the potential for transmission during pregnancy and childbirth being very high. Based on RI Minister of Health Regulation No. 52 of 2017 concerning the Elimination Program for Transmission of HIV, Syphilis and Hepatitis B from Mother to Child or often called " Triple Elimination " which aims to stop transmission from mother to child by laboratory examination of pregnant women at least once during pregnancy. The aim of this research is to determine the results of the Triple Elimination Screening examination of pregnant women of healthy reproductive age in the first trimester at the Lebdosari Community Health Center based on parity, education and employment. This is an observational analytical study with a cross sectional approach. Results from 49 pregnant women, all of them were non-reactive (100%) to HIV testing. Syphilis examination showed that 1 pregnant woman (2%) was reactive and 48 pregnant women (98%) were non-reactive. Heptaitis B examination showed that 1 pregnant woman (2%) was reactive and 48 pregnant women (98%) were non-reactive.